1998
DOI: 10.1016/s0168-6445(98)00008-4
|View full text |Cite
|
Sign up to set email alerts
|

The intracellular life of Chlamydia psittaci: how do the bacteria interact with the host cell?

Abstract: Throughout the life of any organism interactions with the surrounding environment are always taking place, a process that leads to evolution. Chlamydia psittaci is an obligate intracellular parasite, but it must also be capable of extracellular survival in order to search for new host cells. Therefore, these peculiar prokaryotes have evolved two different particles and a unique developmental cycle that, together with a series of not yet fully understood interactions with their host cells, allow them to fulfil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 84 publications
0
9
0
Order By: Relevance
“…In cultured epithelial cells, the doubling time of this species is ∼ 1.8 h (Binet and Maurelli, ). Like C. trachomatis , C. psittaci develops in a vacuole located in the host perinuclear region in the proximity of the Golgi, and upon nutrient deprivation, enters a persistent state (Moulder et al ., ; Escalante‐Ochoa et al ., ; Beeckman and Vanrompay, ). To further probe the competition between the bacterium and Toxoplasma during a co‐infection, we co‐infected epithelial cells with the virulent fast‐growing RH stain of Toxoplasma and the fast‐growing C. psittaci for 24 h and 40 h. Toxopasma was unable to develop properly during a co‐infection with C. psittaci , regardless of the number of inclusions in the cell or of the PV location within the cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In cultured epithelial cells, the doubling time of this species is ∼ 1.8 h (Binet and Maurelli, ). Like C. trachomatis , C. psittaci develops in a vacuole located in the host perinuclear region in the proximity of the Golgi, and upon nutrient deprivation, enters a persistent state (Moulder et al ., ; Escalante‐Ochoa et al ., ; Beeckman and Vanrompay, ). To further probe the competition between the bacterium and Toxoplasma during a co‐infection, we co‐infected epithelial cells with the virulent fast‐growing RH stain of Toxoplasma and the fast‐growing C. psittaci for 24 h and 40 h. Toxopasma was unable to develop properly during a co‐infection with C. psittaci , regardless of the number of inclusions in the cell or of the PV location within the cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the phenotype of the host cell has an important bearing on the uptake of heat-treated organisms. Multiple means of chlamydial attachment to host cells exist, and heat-treated C. psittaci can enter murine macrophages and subsequently form vacuoles that differ from those induced by untreated, infectious organisms [33]. Therefore, although inclusions were not observed by conventional staining in the ovine macrophages or ovine ST-6 cells exposed to heat-treated organisms, it is possible that the chlamydiae were present in a morphologically altered form [34].…”
Section: Identification Of the Early Release Of Cytokines By Cells Inmentioning
confidence: 99%
“…Such changes could be attributed to embolic dissemination of chlamydial infection from placenta (Buxton et al, 1990) as indicated by the presence of elementary bodies in the liver of aborted foeti. The initial interaction of Chlamydia with the host cells begins with the attachment of elementary bodies to the cells followed by phagocytosis within membrane limited vacuole called inclusion which don't fuse with lysosomes of cells and explain the survival of the organism in the intracellular environment (Escalante-Ochoa et al, 1998).…”
Section: Discussionmentioning
confidence: 99%